2015
DOI: 10.1186/s12885-015-1317-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic intervals before and after implementation of cancer patient pathways – a GP survey and registry based comparison of three cohorts of cancer patients

Abstract: BackgroundFrom 2008, Danish general practitioners could refer patients suspected of having cancer to standardised cancer patient pathways (CPPs).We aimed to compare the length of the diagnostic interval in 2010 with the length of the diagnostic interval before (2004/05) and during (2007/08) the implementation of CPPs in Denmark for all incident cancer patients who attended general practice prior to the cancer diagnosis.MethodsGeneral practitioner questionnaires and register data on 12,558 patients were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 32 publications
3
70
0
1
Order By: Relevance
“…9 Good access to primary care could be a factor in providing improved diagnosis of cancer, although evidence that reform of access to specialist assessment could reduce time to diagnosis is stronger. 303 By contrast with this view, evidence showed an association between low cancer survival and the strength of the gatekeeper system, although other country-level factors (such as service organisation) might also be involved. 44 Such an association suggests that, in some health-care systems, the gatekeeper is rationing the use of investigations by setting a high threshold for referral.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…9 Good access to primary care could be a factor in providing improved diagnosis of cancer, although evidence that reform of access to specialist assessment could reduce time to diagnosis is stronger. 303 By contrast with this view, evidence showed an association between low cancer survival and the strength of the gatekeeper system, although other country-level factors (such as service organisation) might also be involved. 44 Such an association suggests that, in some health-care systems, the gatekeeper is rationing the use of investigations by setting a high threshold for referral.…”
mentioning
confidence: 95%
“…[304][305][306] In Denmark, the diagnostic interval has shortened signifi cantly, and direct access to investigations has been appropriately used. 303,307 Progress can also be made by technological innovation in point-of-care testing and detailed clinical audit studies. However, any system making referrals that are contingent on the presence of symptoms with high positive predictive values risks delays in the diagnosis of those with less specifi c symptoms.…”
mentioning
confidence: 99%
“…24,25 Unfortunately, in the same period, a longer delay has been observed for patients not referred in an NCPP. It has therefore been suggested that the NCPPs have benefited only patients with cancer-specific symptoms and potentially may do more harm than good to patients with unspecific symptoms who are not referred in the NCPP.…”
Section: Discussionmentioning
confidence: 91%
“…We observed that crude odds for ''no primary surgery'' were significantly higher among patients with comorbidity (CCI = 1: OR, 1. 24 Univariate and multivariate logistic regression analyses for the association between system delay and comorbidity are presented in Table 5. No significant association between any level of comorbidity and system delay was observed for patients treated with NACT in neither univariate nor adjusted analyses (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…We divided the comorbidity scores into “none” (no recorded disease), “moderate” (score of 1 or 2) and “high” (score of 3 or more) [15]. …”
Section: Methodsmentioning
confidence: 99%